Non-motor Behavioral Alterations of PGC-1α-Deficient Mice – A Peculiar Phenotype With Slight Male Preponderance and No Apparent Progression - Szalardy, Levente; Molnar, Mate F.; Zadori, Denes; Cseh, Edina K.; Veres, Gabor; Kovacs, Gabor G.; Vecsei, Laszlo; Klivenyi, Peter (Frontiers in Behavioral Neuroscience, 2018)
Dysfunction of peroxisome proliferator-activated receptor gamma coactivator-1alpha (PGC-1α) has been linked to various neurodegenerative and neuropsychiatric disorders; however, reports on psychic behavioral alterations on PGC-1α-deficient animals are sparse. The present study revisited prior observations of anxiety-related, depression-related, and hippocampal memory-related observations having been made on different PGC-1α-deficient murine strains, in a large-scale analysis on whole-body full-length (FL-)PGC-1α-deficient mice. The examinations were performed on animals covering a wide age range enrolled from both genders, and included paradigms such as the open-field, elevated plus maze, light-dark box, tail suspension test, and spatial recognition two-trial Y-maze. The findings revealed no signs of previously reported anxiety-like behavior, but revealed an unexpected phenotype with decreased anxiety behavior consistent throughout different paradigms, with slight male preponderance. This was associated with despair-like anhedonic behavior, consistent with that reported previously, but did not associate with either peripheral or brain alterations in kynurenic acid synthesis, which was previously proposed. Though male FL-PGC-1α-deficient mice tended to perform poorer in the hippocampus-based spatial learning paradigm, the genotype overall was not associated with impairment in spatial memory, contradicting with prior observations. None of the observed alterations deteriorated with age, similarly to motor alterations as reported previously. The most likely contributors of this peculiar phenotype are discussed, with clinicopathological correlations drawn. Being the first to address these behavioral domains within the same PGC-1α-deficient strain, our findings extend the knowledge about the complex in vivo effect of PGC-1α dysfunction and add important notes to research in the field of PGC-1α in connection with neuropsychiatric disorders.